Surface Plasmon Resonances in Silver Nanostars - Reyes Gómez, Faustino; Rubira, Rafael J G [UNESP]; Camacho, Sabrina A. [UNESP]; Martin, Cibely S. [UNESP]; da Silva, Robson R.; Constantino, Carlos J L [UNESP]; Alessio, Priscila [UNESP]; Oliveira, Osvaldo N.; Mejía-Salazar, J Ricardo (My University, 2018)
The recent development of silver nanostars (Ag-NSs) is promising for improved surface-enhanced sensing and spectroscopy, which may be further exploited if the mechanisms behind the excitation of localized surface plasmon resonances (LSPRs) are identified. Here, we show that LSPRs in Ag-NSs can be obtained with finite-difference time-domain (FDTD) calculations by considering the nanostars as combination of crossed nanorods (Ag-NRs). In particular, we demonstrate that an apparent tail at large wavelengths ( λ ≳ 700 nm) observed in the extinction spectra of Ag-NSs is due to a strong dipolar plasmon resonance, with no need to invoke heterogeneity (different number of arms) effects as is normally done in the literature. Our description also indicates a way to tune the strongest LSPR at desired wavelengths, which is useful for sensing applications.
Keywords: Ag nanostars; metallic nanoparticles; plasmonic biosensing